Preventive Maintenance Analysis Using Monte Carlo Simulation and Failure Mode and Effect Analysis (FMEA) - Afdal, Zulfani Aflah; Linarti, Utaminingsih (Jurnal Ilmiah Teknik Industri, 2023)
Filter - 2321 is one of the critical components in the production department III A phosphoric acid plant of PT Petrokimia Gresik. Critical components mean that if the filter-2321 is damaged, the production process will stop (Shutdown). Filter-2321 is the highest damaged component that affects the production process is stopped, therefore this study was conducted in order to analyze the causes of failure and improve the value of reliability by using monte carlo and FMEA simulation methods. The first step is to calculate the actual reliability value to determine the effectiveness of the maintenance system that has been implemented by the company. Furthermore, monte carlo simulation reliability simulation and determine the preventive maintenance interval, thus increasing the reliability of the filter-2321. FMEA is used to analyze the cause of the damage and determine the RPN (risk priority number) in failure mode. the results of this study is the value of the actual reliability of the filter-2321 of 30.8264% with MTBF of 1050.99 hours, this value is still too far from the value of the reliability of SII (Indonesian industrial standard) of 70%. The result of RPN (Risk Priority Number) assessment obtained from failure mode and effect analysis is, that the highest value is found in the damaged torque module of 135 and failure mode bearing fix damaged of 135. The suggestion to increase the reliability value is to perform preventive maintenance at intervals of 438.60 hours to increase the reliability value, taking into account the results of the analysis of the causes of the damage that occurred using FMEA.